“The Word for the New Year” by Archimandrite Anastasius (Alexandrov): Speech-Behavioral Analysis - A.Ju. Chernysheva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the speech-behavioral analysis of the “Word for the New Year” by Archimandrite Anastasius (Alexandrov) commenting on the commonly accepted greeting “Wish you Happy New Year and happiness” by comparing the ephemeral and eternal values of communication. The research is based on the central notion of the speech-behavioral concept developed by E.M. Vereshchagin and V.G. Kostomarov, i.e., speech-behavioral tactics (which is understood as a behavior of the speaker, having homogeneous illocution and implementation, aimed at the achievement of the strategic perlocutionary effect), as well as culturally significant characteristics of the speech-behavioral tactics: 1) correlation with the notion of sapientema (a priori and non-verbal inherent consciousness), 2) expression at the deep level of integrated meaning-intention, as well as existence of the verbal implementations at the superficial level, 3) sociality and clichéd character. This paper aims to identify the speechbehavioral tactics used by Archimandrite Anastasius, indicating different understanding of happiness in the atheist and Orthodox cultures. The objectives of the study are as follows: 1) selection of the groups of speech-behavioral tactics, indicating the ephemeral and eternal values; 2) listing of verbal implementations of these tactics; 3) comparison of the concept of happiness in the atheist and Orthodox cultures. The culturological method has been used as the main research method. The practical significance of the paper lies in the fact that its materials can be used in specialized courses on cultural linguistics and to be of interest for specialists in intercultural communication. The paper is of high value, because the historical component of the speech-behavioral tactics used by Archimandrite Anastasius, who raised questions about false and true communicative values in the early 20th century, remains relevant in our time. As a result of the study, groups have been singled out representing the speech-behavioral tactics of debunking the desire for wealth, pleasure, fame and power, fetish of knowledge, carnal attachments, as well as a group of such speech-behavioral tactics that appeal to faith in the God. The specific model of the concept of happiness in the Orthodox culture, which includes the idea of fellowship with the God in the secular understanding of happiness as an earthly bliss, has been emphasized.